Synthetic Cyclolipopeptides Selective against Microbial, Plant and Animal Cell Targets by Incorporation of D-Amino Acids or Histidine - Vilà, Sílvia (PLoS One, 2016)
Cyclolipopeptides derived from the antimicrobial peptide c(Lys-Lys-Leu-Lys-Lys-Phe-Lys-Lys-Leu-Gln) (BPC194) were prepared on solid-phase and screened against four plant pathogens. The incorporation at Lys(5) of fatty acids of 4 to 9 carbon atoms led to active cyclolipopeptides. The influence on the antimicrobial activity of the Lys residue that is derivatized was also evaluated. In general, acylation of Lys(1), Lys(2) or Lys(5) rendered the sequences with the highest activity. Incorporation of a D-amino acid maintained the antimicrobial activity while significantly reduced the hemolysis. Replacement of Phe with a His also yielded cyclolipopeptides with low hemolytic activity. Derivatives exhibiting low phytotoxicity in tobacco leaves were also found. Interestingly, sequences with or without significant activity against phytopathogenic bacteria and fungi, but with differential hemolysis and phytotoxicity were identified. Therefore, this study represents an approach to the development of bioactive peptides with selective activity against microbial, plant and animal cell targets. These selective cyclolipopeptides are candidates useful not only to combat plant pathogens but also to be applied in other fields.